Implementasi Pembelajaran Bahasa Indonesia Berbasis Karakter Kerja Sama - Mulyani, Ani Sri; Nurishlah, Laesti; Br. Tarigan, Linda Fahira (Peneliti.net, 2021)
The nature of Indonesian learning is not only about mastering the rules of grammar and spelling, but also about developing students' ability to think critically, communicate effectively, and appreciate Indonesian culture and identity. This study aims to implement cooperation-based character education on Indonesian subjects. The research method used is library research with a qualitative approach. The results showed that cooperative-based Indonesian learning encourages more active student involvement in the learning process. They feel more involved and play an active role in achieving learning goals. The implementation of cooperative character education helps students to develop essential cooperation skills, such as the ability to listen, share ideas, and work together in achieving common goals. Through collaboration in Indonesian learning, students can improve their communication skills in Indonesian. They learn to articulate ideas, express opinions, and interact with fellow students in clear, effective, and respectful ways.